2016
DOI: 10.1002/hed.24369
|View full text |Cite
|
Sign up to set email alerts
|

Indications, reconstructive techniques, and results for total glossectomy

Abstract: Laryngeal preservation in the context of advanced tumors of the tongue without supraglottic invasion carried similar oncologic results to total glossectomy with laryngectomy, but offers a better phonatory function. However, it is usually associated with a higher gastrostomy dependency ratio. A scrupulous selection of candidates is mandatory. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2004-E2010, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The survival figures in our study concur with others. According to many published studies, the survival after total glossectomy has remained unsatisfactory and a review by Vartanian et al concluded, that for this particular patient group, a 5-year OS above 25% in most series can be considered acceptable [3,[8][9][10][11]. In univariate analysis, we found only high CCI to predict poor survival.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The survival figures in our study concur with others. According to many published studies, the survival after total glossectomy has remained unsatisfactory and a review by Vartanian et al concluded, that for this particular patient group, a 5-year OS above 25% in most series can be considered acceptable [3,[8][9][10][11]. In univariate analysis, we found only high CCI to predict poor survival.…”
Section: Discussionmentioning
confidence: 53%
“…As in our material, anterolateral thigh-free flap (ALT) and vertical rectus abdominis myocutaneous-free flap (VRAM) are the flaps most often used to reconstruct total glossectomy defects [2,8,9,11,[16][17][18]. To optimize functional results, several technical aspects have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant functionality of neural anastomosis has been widely questioned, especially when correlated to postoperative RT . Indeed, although the preservation from muscular atrophy is often recognized as a result of this procedure, in 2016 many still doubted its potential to restoring a contractile function .…”
Section: Discussionmentioning
confidence: 99%
“…The resultant functionality of neural anastomosis has been widely questioned, especially when correlated to postoperative RT. 14,15 Indeed, although the preservation from muscular atrophy is often recognized as a result of this procedure, in 2016 many still doubted its potential to restoring a contractile function. 14 However, evidence exists in the literature that postoperative RT has no negative effects on reinnervation, 5,16,17 and that results concerning the efficacy of nerve repair in irradiated patients are similar to those of other series of neural repair in patients who did not receive postoperative RT.…”
Section: Discussionmentioning
confidence: 99%
“…Larger surgical defect areas are usually reconstructed with flap/graft to restore normal function [ 46 ]. The effect on the intelligibility and quality of speech was more pronounced in these surgically reconstructed cases due to the reduced extensibility of the grafted tissue which may lead to decreased tongue mobility.…”
Section: Post-glossectomy Oral Cancer and Speech Difficultiesmentioning
confidence: 99%